The impact of mammalian target of rapamycin inhibition on bone health in postmenopausal women with hormone receptor-positive advanced breast cancer receiving everolimus plus exemestane in the phase IIIb 4EVER trial - Hadji, Peyman; Marmé, Frederik; Schneeweiss, Andreas (Journal of bone oncology, 2019)
Background - Breast cancer and its treatments are associated with a detrimental effect on bone health. Here we report the results of an exploratory analysis assessing changes in levels of biomarkers of bone metabolism in patients enrolled in the phase IIIb 4EVER study. - Methods - The 4EVER trial investigated everolimus in combination with exemestane in postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative locally advanced or metastatic breast cancer. In this prespecified exploratory analysis, changes in biomarkers of bone turnover were assessed in patients from baseline to weeks 4, 12, and 24. The serum bone markers assessed were procollagen type 1 N-terminal propeptide (P1NP), C-terminal cross-linking telopeptide of type 1 collagen (CTX), osteocalcin, parathyroid hormone (PTH), and 25-hydroxyvitamin D (25-OH-vitamin D). On-treatment changes in bone markers over time were described per subgroup of interest and efficacy outcomes. - Results - Bone marker data were available for 241 of 299 enrolled patients. At the final assessment, P1NP, osteocalcin, PTH, 25-OH-vitamin D (all P<0.001), and CTX (P=0.036) were significantly decreased from baseline values per the Wilcoxon signed-rank test. At the last assessment (24 weeks or earlier), levels of serum CTX and PTH were significantly lower (P=0.009 and P=0.034, respectively) among patients with vs. without prior antiresorptive treatment (ART). Serum CTX levels were significantly lower (P<0.001), and 25-OH-vitamin D concentrations significantly higher (P=0.029), at the last postbaseline assessment in patients receiving concomitant ART vs. those without ART. Changes from baseline in PTH and 25-OH-vitamin D concentrations to the final assessment were significantly smaller in patients with prior ART. Lower baseline serum concentrations of osteocalcin and PTH were associated with clinical response (partial vs. non-response) at 24 weeks. High serum levels of CTX and P1NP at baseline were risk factors for progression at 12 weeks. - Conclusions - These exploratory analyses support use of everolimus plus exemestane for the treatment of postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer, and add to the body of evidence suggesting a potentially favorable impact of everolimus on bone turnover. - Trial registration - NCT01626222. Registered 22 June 2012, https://clinicaltrials.gov/ct2/show/NCT01626222.
Available online 2 October 2018
Gesehen am 11.07.2019